Freshwater pearl mussel as indicators of Swedish streams - a comparison between freshwater pearl mussel and biological quality elements - Forsell, Kristin (2014)
The freshwater pearl mussel (Margaritifera margaritifera) is a large freshwater mussel. Because of its sensitivity to human impact, such as eutrophication, acidification and alterations of hydromorphology, the species is considered as a robust indicator of stream water quality and biodiversity. Moreover, due to the species complex life cycle, including a larval stage on the gills of salmon and trout, and sensitivity of early life stages, regeneration is often used as an indicator. The freshwater pearl mussel is also used in the expert judgement of status classification of benthic invertebrates according to the European Water Framework Directive.